Implikasi Emotionally Freedom Tehnique untuk Mengatasi Kecemasan Santri dalam Public Speaking di Pesantren Pulau Bangka - Nurviyanti Cholid; Wahyudi; Pebri Yanasari; Yogi Christian; Iza Zumrotul Zahro (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2026)
Problem: The ability to speak (muhadharah) is a mandatory competency in Islamic boarding schools, but many students on Bangka Island experience psychological barriers in the form of excessive anxiety (stage fright). This anxiety manifests in physical symptoms and loss of concentration when speaking in public. Objective: This community service activity aims to equip students with the independent technique of Emotional Freedom Technique (EFT) to reduce the intensity of anxiety and increase self-confidence when performing public speaking. Method: The implementation of the activity uses a participatory training method that includes three stages: (1) Socialization of the concept of energy psychology and anxiety mechanisms; (2) Independent practice of tapping techniques on 18 meridian points of the body; and (3) Post-intervention speech simulation assistance. The target of the service is middle-level students at one of the Islamic boarding schools on Bangka Island. Results: This activity succeeded in increasing students' understanding of emotional management by 85%. Based on self-evaluation, the majority of students reported a decrease in physical symptoms of anxiety (such as cold sweats and tremors) after practicing EFT. Students now have a self-help tool they can use anytime before stepping onto the pulpit. Conclusion: The implementation of EFT has positive implications as a practical and effective solution for overcoming students' psychological barriers. It is recommended that Islamic boarding school administrators adopt this program as part of their extracurricular da'wah activities to optimize students' rhetorical potential.Keywords: Emotional Freedom Technique, Speaking Anxiety, Public Speaking, Students, Community Service.